2003
DOI: 10.1046/j.1365-2753.2003.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to physicians’ decisions to discuss hospice: insights gained from the United States hospice model

Abstract: Due to its comprehensive and cost-saving design, hospice has become a critical component of health care. Physicians have become the primary gatekeepers to information on hospice and sources of referral to hospice. However, many physicians do not discuss hospice options until late in the disease course, when patients and their families are no longer able to benefit from hospice services. Although physicians, as well as patients and hospice personnel, cite patient and hospice structure factors as barriers, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 27 publications
3
64
0
1
Order By: Relevance
“…38 Our data also demonstrate that very few patients refused hospice care. Physicians often cite patient reluctance to consider hospice as a major barrier to hospice referral [39][40][41][42] ; however, our data suggest this may not need to be a concern.…”
Section: Discussionmentioning
confidence: 55%
“…38 Our data also demonstrate that very few patients refused hospice care. Physicians often cite patient reluctance to consider hospice as a major barrier to hospice referral [39][40][41][42] ; however, our data suggest this may not need to be a concern.…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, physicians may be reluctant to discuss hospice with patients because of difficulty communicating that a disease-specific treatment is futile or no longer effective, or they simply may not feel the patient will be understanding or receptive to the idea of palliative care or hospice. 8 Despite perceptions of the clinician regarding timing of hospice referral, retrospective studies have demonstrated that hospice referrals that are made too early are very rare, and are far outnumbered by referrals that come too late. 1,6 Recent data showed that a phone ARNP intervention can mitigate the decline in psychological well-being experienced by metastatic cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] However, patients who have a better understanding of their prognosis and realistic expectations are more likely to receive better care and are less likely to experience end-of-life regrets. [13][14][15][16] Moreover, endof-life discussions between patient and provider do not appear to increase psychological distress, and patients who have these discussions have been shown to have a better understanding of illness severity. 17 Despite this support for more transparency with respect to end-of-life discussions, there is overwhelming evidence that palliative care is not routinely integrated into end-of-life cancer care.…”
Section: Introductionmentioning
confidence: 99%